UANG JAPUIK DALAM TRADISI PERNIKAHAN MASYARAKAT PARIAMAN: TELAAH FILOSOFIS, HISTORIS, SOSIAL, EKONOMI, DAN PERSPEKTIF EKONOMI ISLAM - Febri Yolanda, Dwi; Fahlefi, Rizal; Lutfi, Ahmad (JSE: Jurnal Sharia Economica, 2026)
The tradition of uang japuik in the Pariaman community is often misunderstood as a form of “purchasing a groom” or as an economic burden imposed on women. In reality, this tradition carries profound philosophical meaning as a symbol of respect, honor, and social responsibility within the Minangkabau matrilineal system. This article seeks to correct these misconceptions through a descriptive qualitative approach that integrates field data, academic literature, official documentation from Indonesia’s Intangible Cultural Heritage (WBTB), and Islamic economic analysis. The findings reveal that uang japuik functions as both a social and spiritual mechanism that strengthens inter-clan relationships, regulates cultural economic redistribution, and maintains the balance of honor (marwah) between the male and female parties. From an Islamic perspective, this tradition qualifies as ‘urf shahih, as it is practiced based on mutual agreement, sincerity, and shared benefit. Thus, uang japuik is not a transactional economic practice, but rather a harmonious integration of custom and religious principles affirming the Minangkabau philosophy: adat basandi syarak, syarak basandi Kitabullah.